Introduction to econometrics - Maddala G. S (Wiley, 2012)
Introduction to econometrics has been one of the most important textbooks in its field influencing several generations of students. G.s maddala died in 1999 whilst he was completing the manuscript for the third edition. The time is right for a new edition and kajal lahiri is the ideal person to update the text. He was one of maddala's closest colleagues and also has a high profile in the econometrics profession and is particularly noted for his work on panel data. The third edition of introduction to econometrics has been translated into hungarian, japanese and portuguese. Part i introduction and the linear regression model · what is econometrics? · statistical background and matrix algebra · simple regression · multiple regression part ii violation of the assumptions of the basic regression model · heteroskedasticity · autocorrelation · multicollinearity · dummy variables and truncated variables · simultaneous equation models · diagnostic checking, model selection, and specification testing · errors in variables part iii special topics · introduction to time-series analysis · models of expectations and distributed lags · vector autoregressions, unit roots, and cointegration · panel data analysis · small-sample inference: resampling methods